Pengembangan Media E-Komik Edukatif pada Mata Pelajaran IPAS Kelas V Sekolah Dasar (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to develop educational e-comic media as a learning medium for science and science subjects in class V SDN 07 Pulau Air using the ADDIE model which includes five stages, namely Analysis, Design, Development, Implementation and Evaluation. Data collection was carried out by observation, interviews, questionnaires, and documentation. Data analysis in the research carried out validity tests, practicality tests and effectiveness tests. The validity test was carried out by 3 validators consisting of 1 material validator and 2 media validators. Product trials were carried out by 25 class V.A students at SDN 07 Pulau Air with the aim of finding out the practicality of the product being developed, and effectiveness testing was carried out by distributing pretest and posttest questions. The results of research on the development of educational e-comic media obtained an average score for material of 4.92 with very suitable criteria, and 4.95 for media with very suitable categories. The students' practicality test results obtained a total average of 4.5 in the very practical category. The results of the effectiveness test obtained t_count of 11.52 and t_table= 2.064. Thus we get t_count > t_table. Based on the results of validity, practicality, and effectiveness tests, it can be concluded that the use of digital e-comic media in science and science learning is very suitable for use and has a significant effect on the learning process